2016
DOI: 10.1089/pho.2015.4077
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Diode Irradiation (640 nm) Regulates Keratinocyte Migration and Cytoskeletal Reorganization Via Hypoxia-Inducible Factor-1α

Abstract: LED irradiation may increase keratinocyte migration via HIF-1α-dependent cytoskeletal reorganization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…It has been indicated that AMPK pathway is involved in cell migration in many types of cancer cells [19,31], and previous study has confirmed that the inhibition of AMPK promotes the mobility of HaCaT cells [17]. Furthermore, hypoxic preconditioning also promotes the migration of keratinocytes through AMPK pathway [32,33]. In this study, we confirmed that endogenous EF reduced the CD9 expression in keratinocytes and inhibited AMPK pathway.…”
Section: Discussionsupporting
confidence: 82%
“…It has been indicated that AMPK pathway is involved in cell migration in many types of cancer cells [19,31], and previous study has confirmed that the inhibition of AMPK promotes the mobility of HaCaT cells [17]. Furthermore, hypoxic preconditioning also promotes the migration of keratinocytes through AMPK pathway [32,33]. In this study, we confirmed that endogenous EF reduced the CD9 expression in keratinocytes and inhibited AMPK pathway.…”
Section: Discussionsupporting
confidence: 82%
“…PBM, delivered as low-level laser, has been shown to have a dramatic effect on the cytoskeleton structure of nerve cells, with the rapid formation of transient varicosities, and consequent nerve blockade for pain relief. [45][46][47][48][49] PBM also affects the cytoskeleton of other cells besides neurons, such as epithelial cells, 50 keratinocytes, 51 and fibroblasts, 52 and has been shown to have effects on protein conformation, including calcium ion channels. [53][54][55] PBM also has an effect on brain oscillation patterns, with changes to alpha, beta, gamma, delta, and theta waves in both mice 56 and humans 57 (El Khoury, et al, unpublished observations) and effects on the default mode network.…”
Section: Photobiomodulationmentioning
confidence: 99%
“…Huang et al reported increased migration with LED 640 nm at a dose of 12 J/cm 2 compared to the use of 24 J/cm 2 . 24 This same author performed a cell motility test and identified an increase in cell trajectory of 41.9% in applying 12 J/cm 2 and 18.3% with 24 J/cm 2 .…”
Section: Studied Model Light Outcomesmentioning
confidence: 98%
“…Huang et al 24 In vitro: Human keratinocyte cells (primary) 640 nm; 12 or 24 J/cm 2 ; 30 mW/ cm 2 ; 6.40 s; 1 day LED increases motility, migration, and HIF-1α protein with induction of F-actin reorganization.…”
Section: Rohringer Et Al In Vitro: Human Umbilical Vein Endothelial C...mentioning
confidence: 99%
See 1 more Smart Citation